ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMAHAMAN PELAKU UMKM DALAM PENYUSUNAN LAPORAN KEUANGAN MENURUT STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK EMKM) (Pada UMKM di Kecamatan Dukuh Pakis Kota Surabaya) - Anggraini, Rizka Ivantri; Sumanto, Agus (SUSTAINABLE, 2023)
The aim of the written research is to determine the influence of educational background, business size and age, availability of information, and business reach on UMKM understanding in preparing financial reports in accordance with SAK EMKM. The research sample was 65 UMKM in various industries registered with the Office of Cooperatives and UMKM in Dukuh Pakis District. Purposive sampling, namely the use of sampling methods. The sample in the study was 46 MSMEs, each of which had to fulfill two conditions: 1) it must mean that UMKM actors are active in the Dukuh Pakis District representing various industrial sectors; and 2) they must have been in business for at least two years. Respondents are given a questionnaire to fill out, and this is where the main data is collected. Quantitative analysis is a technique used in analyzing data. The results of the study show: (a) SAK EMKM shows that the education level of UMKM actors does not affect the understanding of making financial reports, with a t-value of -0.575 and a significant value of 0.568; (b) SAK EMKM with a t-count value of 3.455 and a significant value of 0.001 shows that education has a positive and significant influence on the understanding of UMKM actors in producing financial reports; (c) According to SAK EMKM, the size of the business has no influence on how well UMKM actors understand, with a t-value of 1.402, a significant value of 0.169; (d) the age of the business also has no effect on how well UMKM players understand with a t-value of -0.544, a significant value of 0.590; and (d) the dissemination of information and socialization also has no effect on how well MSME actors understand.